Medicinal plants from Southeast Asia affecting the reproductive system - Rahmawati, Naili; Benjamin, Mohammad Amil Zulhilmi; Wahyuni, Tutik Sri; Mohd Sani, Mohd Hijaz; Abdul Kadir, Arifah; Abdullah, Muhammad Nazrul Hakim; Ahmed, Qamar Uddin; Zakaria, Zainul Amiruddin (Elsevier B.V. (UK), 2025)
Medicinal plants significantly influence the reproductive system, exhibiting both antifertility and fertility properties. This review compiles information on the effects of medicinal plants native to Southeast Asia on reproductive health, specifically focusing on infertility and fertility enhancement in both males and females. Literature was retrieved from reputable databases, including Scopus, PubMed, and Google Scholar, employing targeted search terms related to antifertility and fertility within the context of Southeast Asia. Research on antifertility and fertility has primarily emerged from Indonesia, Malaysia, and Thailand, with additional fertility studies specifically identified in Vietnam. A total of 31 papers documented antifertility and fertility activities, with Indonesia being the most prolific in research output. Key bioactive compounds identified include saponins, which are associated with antifertility, as well as ellagic acid and eurycomanone, both linked to fertility enhancement. This review explores the potential reproductive effects of these plants on various reproductive challenges, providing valuable insights for future research and clinical applications, including the development of environmentally friendly contraceptive drugs and effective infertility treatments. This comprehensive analysis aims to inform practitioners and researchers about the therapeutic potential of these medicinal plants in enhancing reproductive health.